(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
An Ethno-Medicinal survey was carried out in some villages of Juang community in Keonjhar district of Orissa to evaluate the plants used for medicine by them. The investigation was carried out in Juang villages with participant observation, Interview method, case study, snowball sampling and administration of Survey schedules. The study enumerated 32 species belonging to 21 families that are used by them for treatment of common ailments and Healthcare. The plants used for traditional medicines are mostly collected from the forest. It has been revealed that although the Juang concept of disease and treatment revolves around a religious beliefs and practices, they depend on plant medicine to a larger extent, although they are using modern medicine in the current scenario. It has been understood that some of the medicinal plants have become scares in the area due to industrialisation and other activity. Documentation of traditional knowledge on the economy and the uses of these plants may contribute to the germplasm conservation efforts as well as for the new drug development.